2003
DOI: 10.1046/j.1365-2583.2003.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden from the host: Spiroplasma bacteria infecting Drosophila do not cause an immune response, but are suppressed by ectopic immune activation

Abstract: Insects and other arthropods have an effective innate immune system that can clear infections with bacteria and other microorganisms. Despite this ability, one group of bacteria, the spiroplasmas, survive unharmed within the haemolymph of a wide range of arthropod hosts. We investigated the interaction between one member of this clade, a relative of Spiroplasma poulsonii, and the immune system of its Drosophila host. Expression of antimicrobial genes in spiroplasma-infected flies did not differ from wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 18 publications
12
66
3
Order By: Relevance
“…It did not appear that R. peacockii constrained lysozyme or defensin expression by infected tick cells, as infection did not influence expression by infected but otherwise unstimulated cells or decrease the responsiveness of IDE12 or DAE15 cells to bacterial stimulation. Similarly, Spiroplasma infecting D. melanogaster did not upregulate expression of antimicrobial peptides, or prevent upregulation of antimicrobial peptides after stimulation by inactivated E. coli and spores of the entomopathogenic fungus Beauveria bassiana (29). The tickendosymbiont relationship may be synonymous to the Drosophila response to Spiroplasma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It did not appear that R. peacockii constrained lysozyme or defensin expression by infected tick cells, as infection did not influence expression by infected but otherwise unstimulated cells or decrease the responsiveness of IDE12 or DAE15 cells to bacterial stimulation. Similarly, Spiroplasma infecting D. melanogaster did not upregulate expression of antimicrobial peptides, or prevent upregulation of antimicrobial peptides after stimulation by inactivated E. coli and spores of the entomopathogenic fungus Beauveria bassiana (29). The tickendosymbiont relationship may be synonymous to the Drosophila response to Spiroplasma.…”
Section: Discussionmentioning
confidence: 93%
“…Bourtzis et al (28) found that Wolbachia, an endosymbiotic bacterium that infects a wide range of arthropods, did not appear to induce or suppress defensin expression in Drosophila simulans or Aedes albopictus. It is not known how Wolbachia avoids eliciting immune responses, but living inside cells may be an important adaptation that hides Wolbachia from arthropod immune systems (29). In nature, R. peacockii inhabits the ovaries of female D. andersoni and is rarely found in hemolymph (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although the bacterium is widely distributed in different tissues, it accumulates at high concentrations in haemolymph. The presence of Spiroplasma does not induce expression of any of seven antimicrobial genes in Drosophila 55 . The absence of an immune response does not result from immunosuppression, as the response can be induced by septic injury in Drosophila melanogaster that is already infected by Spiroplasma 55 .…”
Section: Box 3 | Heritable Microorganismsmentioning
confidence: 91%
“…The presence of Spiroplasma does not induce expression of any of seven antimicrobial genes in Drosophila 55 . The absence of an immune response does not result from immunosuppression, as the response can be induced by septic injury in Drosophila melanogaster that is already infected by Spiroplasma 55 . The absence of a response upon Spiroplasma infection results from an absence of elicitors; the lack of wall structure, including peptidoglycan, might explain the success of Spiroplasma in colonizing many species of insects.…”
Section: Box 3 | Heritable Microorganismsmentioning
confidence: 91%
See 1 more Smart Citation